Solvation of ions in helium. Issue 4 (1st October 2020) - González-Lezana, Tomás; Echt, Olof; Gatchell, Michael; Bartolomei, Massimiliano; Campos-Martínez, José; Scheier, Paul
Abstract : We review the solvation of atomic, molecular or cluster ions in HNDs. After briefly discussing the properties of snowballs in bulk helium we consider experimental conditions for the efficient synthesis of charged, doped HNDs. We show that the cluster ions observed in conventional mass spectrometers originate from fission of highly charged HNDs. The ionization threshold of HNDs doped with alkalis reveals the minimum cluster size required for full immersion. The abundance distributions of He N X ± ions frequently reveal local anomalies or magic numbers. We demonstrate that the abundance is approximately proportional to the evaporation energy. Observed and calculated magic numbers will be compiled, including data for ions solvated in molecular hydrogen. Alternative methods to forming He N X + that do not employ HNDs will be summarized. Electronic excitation spectra of C 60 + and polycyclic aromatic hydrocarbon ions reveal the properties of the helium adsorption layer in quantitative detail. Next we discuss theoretical efforts to describe the interaction between ions and helium. We close with summarizing the size dependence of physical quantities computed for atomic alkali and alkaline earth cations in helium, such as binding energy, superfluid fraction, structural order, radial density profiles, and the existence of first and higher solvation shells.